Tree growth response to the 2022 compound drought and heatwave on the eastern Qinghai-Tibetan Plateau - Zhenzhen Wang; Meiying Ji; Jianqiong Luo; Mingfang Zhang; Ning Miao (Forest Ecology and Management, 2025)

Effects of light intensity on Opsin4 , Opsin5, and Pax6 expressions of the sea urchin Strongylocentrotus intermedius - Mingfang Yang; Yushi Yu; Jingyun Ding; Jia Luo; Jiangnan Sun; Fangyuan Hu; Yaqing Chang; Chong Zhao (Marine Ecology, 2020)
The detection of light intensity and subsequent phototaxis are essential for the fitness of sea urchins in intertidal and shallow subtidal waters, where light intensity varies in accordance with the depth and other hydrographic conditions. The molecular basis of photoresponse, however, remains largely unknown. We compared the expression of SiOpsin4 , SiPax6, and SiOpsin5 among tube feet, coelomocytes, gonads, and gut of the sea urchin Strongylocentrotus intermedius . All three genes showed the significantly highest expression in tube feet. To test whether r‐opsin genes (for example, Opsin4 ) and Pax6 in tube feet, rather than chaopsin genes (for example, Opsin5 ), are involved in the molecular responses to light intensity, we investigated the expression of Opsin4 , Pax6, and Opsin5 among four light intensities. Both Opsin4 and Pax6 expressions were significantly higher in the sea urchins at 1,500 lx than at 100, 300, and 700 lx, indicating a co‐upregulation of Opsin4 and Pax6 expressions in sea urchins exposed to the high light intensity (for example, 1,500 lx). However, there was no significant difference of SiOpsin5 expression among the four light intensity groups. Consistent with our hypothesis, there was no significant difference in either Opsin4 or Pax6 expression between the two light intensity environments (low light intensity environment: 50–100 lx; high light intensity environment: 330–1400 lx). This indicates that positive phototaxis and negative phototaxis probably regulate the expression of Opsin4 and Pax6 to a similar level when sea urchins are exposed to the high and low light intensities, respectively. The present study provides new insights into the molecular basis of light intensity detection and subsequent phototaxis of eyeless species.

The NPR1 homolog GhNPR1 plays an important role in the defense response of Gladiolus hybridus - Xionghui Zhong; Lin Xi; Qinglong Lian; Xian Luo; Ze Wu; Shanshan Seng; Xue Yuan; Mingfang Yi (Plant Cell Reports, 2015)

Involvement of Ca2+ and CaM3 in Regulation of Thermotolerance in Lily (Lilium longiflorum) - Xing Cao; Jin Yi; Ze Wu; Xian Luo; Xionghui Zhong; Jian Wu; Muhammad Ali Khan; Yang Zhao; Mingfang Yi (Plant Molecular Biology Reporter, 2013)

Enhancement of biodesulfurization by Pseudomonas delafieldii in a ceramic microsparging aeration system - Xing Lin; Huizhou Liu; Feiyan Zhu; Xuetuan Wei; Qiang Li; Mingfang Luo (Biotechnology Letters, 2012)